Neonatal aortic thrombosis: a life-threatening complication of umbilical artery catheterisation - Ying, Thay Wee; Abang Abdullah, Aisha Fadhilah; Mohamed Jamli, Faizah; Zainudin, Zurina (Malaysian Medical Association, 2020)
Umbilical artery catheterisation is considered the standard of care for arterial access in neonatal intensive care unit. It is routinely used for blood sampling and blood pressure monitoring. Unfortunately, an indwelling umbilical catheter have been associated with thrombotic complication which may result in either partial or complete occlusion of the aorta. We report here our experience in the diagnosis and treatment of a neonate with this condition.